2020
DOI: 10.1002/dc.24557
|View full text |Cite
|
Sign up to set email alerts
|

The importance of risk of neoplasm as an outcome in cytologic‐histologic correlation studies on thyroid fine needle aspiration

Abstract: Background: The introduction of noninvasive follicular thyroid neoplasm with papillary-like nuclear features (NIFTP) altered the practice of thyroid pathology and reduced the risk of malignancy (ROM) associated with the indeterminate categories in the Bethesda system for reporting thyroid cytopathology (TBSRTC). It has been proposed that the evaluation of the risk of neoplasm (RON) is important in cytologichistologic correlation studies. Methods: A total of 5224 thyroid aspirates were performed at our institut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 29 publications
1
7
1
Order By: Relevance
“…The array of our reported RON was quite different than what was reported before 21‐23 (Table 6). The calculated RON for the AUS category in this study was significantly higher than the ROM, while the calculated RON and ROM for the other intermediate categories, SFN and SFM, were comparable.…”
Section: Resultscontrasting
confidence: 86%
See 1 more Smart Citation
“…The array of our reported RON was quite different than what was reported before 21‐23 (Table 6). The calculated RON for the AUS category in this study was significantly higher than the ROM, while the calculated RON and ROM for the other intermediate categories, SFN and SFM, were comparable.…”
Section: Resultscontrasting
confidence: 86%
“…They concluded that the risk of neoplasm is a good index for surgery, and have endorsed conservative treatment with lobectomy for cases that are indeterminate by FNA but suspicious in molecular testing. Their results were more consistent with those of Chen et al and Wu et al 22,23 The lesson learned here is that the management recommendations of BSFRTC should not be taken rigidly, but rather be determined depending on the RON and ROM values on an institutional basis. A RON/ROM ratio close to unity in indeterminate categories is a marker indicative of surgical triaging.…”
Section: Discussionsupporting
confidence: 87%
“…43,44 Some studies reported metabolic syndrome was an independent risk factor for the increased prevalence of thyroid nodular disease and cancer in both sex, however. 21,22 This study demonstrated that the thyroid status and thyroid function test were not significant predictors for the thyroid FNAC outcome. A similar result was obtained in a recently published study conducted in the same region.…”
Section: Discussionmentioning
confidence: 75%
“… 9 , 13 15 Thyroid FNAC management was cost-effective compared with watchful management. 16 Several factors – such as age, 17 female sex, 18 thyroid status, thyroid hormone level, 19 thyroid autoantibodies, 20 metabolic syndrome components, 21 , 22 smoking and alcohol consumption, 23 environmental factors, 18 , 24 diet and nutritional pattern, 25 and genetic factors 26 – have been reported as risk factors associated with thyroid nodular diseases and cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, ROM has been the prominent factor in guiding surgical management and prognostication of patients with thyroid nodules. However, some studies have suggested, especially in light of the categorization of noninvasive follicular neoplasm with papillary-like nuclear features (NIFTP) as a low-risk tumor rather than a malignancy, that a 3-pronged approach in the assessment of cytologic-histologic correlation (including benign, neoplastic, and malignant outcomes) may be beneficial in the future evaluation of the utility of TBSRTC diagnostic categories [22, 23]. As such, both RON and ROM were evaluated in our study.…”
Section: Discussionmentioning
confidence: 99%